(untitled) - Griffin, Laura; 1973- (Thorndike, Maine, 2022)
"When former forensic photographer Miranda Rhoads moves to the seaside town of Lost Beach, shes decided to make her living as a wildlife photographer and put crime scenes behind her. But her plans are quickly upended when one morning, she comes across a couple sleeping in a canoe, entwined in an embrace. Looking closer, she realizes the man and woman arent asleep--theyve been murdered. Detective Joel Breda sets out to find answers--not only about the unidentified victims in the marshy death scene, but also about the aloof and beautiful photographer who seems to know more about his investigation than he does. As they begin to unravel the motivation of a merciless serial killer, Miranda and Joel must race against the clock to make an arrest before the killer can find them first."--
Keywords: Fiction; Fiction; Police; Investigation; Murder; Fiction; Man-woman relationships; Fiction; Women photographers; Texas; Fiction; Romance fiction; Romantic suspense fiction; Detective and mystery fiction; Thrillers (Fiction)